A review of structural brain abnormalities in Pallister‐Killian syndrome. Issue 1 (9th December 2017) - Poulton, Cathryn; Baynam, Gareth; Yates, Clarissa; Alinejad‐Rokny, Hamid; Williams, Simon; Wright, Helen; Woodward, Karen J.; Sivamoorthy, Soruba; Peverall, Joanne; Shipman, Peter; Ravine, David; Beilby, John; et al.
Abstract: Background: Pallister‐Killian syndrome (PKS) is a rare multisystem developmental syndrome usually caused by mosaic tetrasomy of chromosome 12p that is known to be associated with neurological defects. Methods: We describe two patients with PKS, one of whom has bilateral perisylvian polymicrogyria (PMG), the other with macrocephaly, enlarged lateral ventricles and hypogenesis of the corpus callosum. We have also summarized the current literature describing brain abnormalities in PKS. Results: We reviewed available cases with intracranial scans ( n  = 93) and found a strong association between PKS and structural brain abnormalities (77.41%; 72/93). Notably, ventricular abnormalities (45.83%; 33/72), abnormalities of the corpus callosum (25.00%; 18/72) and cerebral atrophy (29.17%; 21/72) were the most frequently reported, while macrocephaly (12.5%; 9/72) and PMG (4.17%; 3/72) were less frequent. To further understand how 12p genes might be relevant to brain development, we identified 63 genes which are enriched in the nervous system. These genes display distinct temporal as well as region‐specific expression in the brain, suggesting specific roles in neurodevelopment and disease. Finally, we utilized these data to define minimal critical regions on 12p and their constituent genes associated with atrophy, abnormalities of the corpus callosum, and macrocephaly in PKS. Conclusion: Our study reinforces the association between brain abnormalities and PKS, and documents a diverse neurogenetic basis for structural brain abnormalities and impaired function in children diagnosed with this rare disorder. Abstract : We report two cases of Pallister‐Killian Syndrome, and conducted a literature review to describe a diverse neuropathological basis for impaired brain function in children diagnosed with this rare disorder.